Small-Molecule Induction Promotes Corneal Endothelial Cell Differentiation From Human iPS Cells - Chen, Jie; Ou, Qingjian; Wang, Zhe; Liu, Yifan; Hu, Shuqin; Liu, Yumeilan; Tian, Haibin; Xu, Jingying; Gao, Furong; Lu, Lixia; Jin, Caixia; Xu, Guo-Tong; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: Corneal endothelial cells (CECs) serve as a barrier and foothold for the corneal stroma to maintain the function and transparency of the cornea. Loss of CECs during aging or disease states leads to blindness, and cell replacement therapy using either donated or artificially differentiated CECs remains the only curative approach. Methods: Human induced pluripotent stem cells (hiPSCs) that were cultured in chemically defined medium were induced with dual-SMAD inhibition to differentiate into neural crest cells (NCCs). A small-molecule library was screened to differentiate the NCCs into corneal endothelial-like cells. The characteristics of these cells were identified with real-time PCR and immunofluorescence. Western blotting was applied to detect the signaling pathways and key factors regulated by the small molecules. Results: We developed an effective protocol to differentiate hiPSCs into CECs with defined small molecules. The hiPSC-CECs were characterized by ZO-1, AQP1, Vimentin and Na+/K+-ATPase. Based on our small-molecule screen, we identified a small-molecule combination, A769662 and AT13148, that enabled the most efficient production of CECs. The combination of A769662 and AT13148 upregulated the PKA/AKT signaling pathway, FOXO1 and PITX2 to promote the conversion of NCCs to CECs. Conclusion: We established an efficient small molecule-based method to differentiate hiPSCs into corneal endothelial-like cells, which might facilitate drug discovery and the development of cell-based therapies for corneal diseases.